2007
DOI: 10.1111/j.1600-0501.2007.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of absorbable membranes on sandwich bone augmentation

Abstract: Within the limit of this study, it is concluded that SBA technique achieved predictable clinical outcomes. The addition of absorbable membranes enhanced bone gain in thickness compared with membrane-treated sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(149 citation statements)
references
References 68 publications
(80 reference statements)
8
140
0
1
Order By: Relevance
“…Indeed, the displacement of the alveolar nerve is technically tough, and this procedure may be associated with certain degree of permanent loss of nerve sensitivity [1, 69]. Different surgical techniques are currently being used to augment the posterior mandible: guided bone regeneration (GBR) and alveolar distraction osteogenesis onlay bone grafting; however, only few of these have been tested in randomized clinical trial (RCT) [10, 11]. Several surgical bone augmentation techniques are related to an unpredictable resorption of the grafted material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the displacement of the alveolar nerve is technically tough, and this procedure may be associated with certain degree of permanent loss of nerve sensitivity [1, 69]. Different surgical techniques are currently being used to augment the posterior mandible: guided bone regeneration (GBR) and alveolar distraction osteogenesis onlay bone grafting; however, only few of these have been tested in randomized clinical trial (RCT) [10, 11]. Several surgical bone augmentation techniques are related to an unpredictable resorption of the grafted material.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible approach is to use an interpositional bone graft [1, 4, 8, 11]. The rationale of the interpositional techniques is based on the theory that biomaterial placed between 2 pieces of pedicled bone with internal cancellous bone will undergo rapid and complete healing and graft incorporation with a lower percentage of resorption.…”
Section: Introductionmentioning
confidence: 99%
“…7 It has been shown in clinical studies that a predictable result with GBR requires certain conditions, such as wound stabilization, and space creation and maintenance. 8 Benic et al 9 reported that 5 out of 14 implants at sites in which GBR had been applied had no buccal bone on radiography at a 7-year follow-up. Thus, it appears that membrane stability and space creation are difficult to achieve in cases of extensive alveolar resorption.…”
Section: Discussionmentioning
confidence: 98%
“…For the control group, percentage bone fill was only 54.64 ± 37.23%; on the contrary, dissimilar results were also noticed without the use of growth factor. 7,28 Overall significant reduction was observed in test groups from baseline to 5 months but was nonsignificant for the control group. This emphasizes the fact that external application of PDGF-BB did stimulate bone regeneration and this has been witnessed as early as 7 days following implant placement in histologic studies of Lynch et al 3 Along with that, it has a crucial role in healing 29 and attracting fibroblasts into the clot.…”
Section: -10mentioning
confidence: 99%
“…Full-thickness flap was reflected using a mid-crestal and vertical incisions, 7 and care was taken to avoid unnecessary trauma to the gingiva of the adjacent teeth. The site was prepared using successive drills; the socket was flushed with sterile normal saline, following which the implant was screwed into the bone with the hex ratchet using insertion torque of 30 to 35 N/cm 2 until the implant was seen flushed with the alveolar bone.…”
Section: Surgical Proceduresmentioning
confidence: 99%